EFEKTIVITAS PENERAPAN SISTEM AKADEMIK TERKOMPUTERISASI : STUDI DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Meily Margaretha; Lina Anatan; T. Elisabeth Cintya Santosa (Universitas Trisakti, 2009)
Competitiveness among universities demands them to give good qualities in education service and physical facilities. One way to achieve the demand is by technology information adoption through online facility service, which is implementation of Sistem Akademik Terkomputedsasi (SAT). This system is adopted in order to facifltate students' academic and administration process and give convenience for student to access information through internet facility.The purposes of the study were to analyze factors that influenced students' attention in using SAT technology and their influence toward degree of SAT adoption. This study was conducted using Technology Acceptance Model (TAM) which is adjusted with the object of the study, namely student self access terminal (SSAT), Self Access Terminal (SSAT) is an academic system computerization where presently used by one private university in Bandung. This system called as Sistem Akademik Terkomputerisasi (SAT).Data collection were collected using questionnaire which given to 320 active college students of one private university in Bandung from different faculties as the respondents. The respondents were chosen using proportionate random sampling. Data can be used in this study were 270 respondents with responds rate 84,4%.All the hypotheses in this study were analyzed using Hierarchical Regressions Analysis. The result shown that almost the hypotheses were supported, excluding the third hypothesis, which shown that risk perception has positive significant influence toward perception of using SAT technology.Keywords : Sistem Akademik Terkomputerisasi (SAT), Technology Acceptance Model (TAM)